The Challenge of Controlling - Osmanagić Bedenik, Nidžara (International Journal of Industrial Engineering and Management, 2015)
Recent years in business have been characterized by a high level of dynamics and complexity. Today’s business problems cannot be solved with traditional methods and approaches from the past. It is clear that a new management architecture, new approaches and new methods are required. Controlling is one of the new approaches which helps management to adapt better to new circumstances, to build vital and vivid organisations, capable of facing new challenges. Controlling with controllers as experts provides proactive and neutral management support in their decision and management process. Not only do more and more theoretical papers and books bring evidence of the rise of controlling, empirical research studies also reflect its broad implementation in practise. Controlling is a success factor, no doubt. In companies in Croatia controlling is a relatively young function with increasing importance, still more intra- than extra-oriented, focused on operative business more than its strategic and normative aspects. Different perspectives in controlling development, e.g. controlling in SME’s, crisis controlling, project controlling, controlling in HR, finance, production as well as controlling in non-profit organisationsand sustainability or ‘green’ controlling are some of its future directions. Article history: Received (30.11.2015); Revised (23.12.2015); Accepted (29.12.2015)